2x + 3y = 2 ........(1)

x - 3y = 7 ..........(2)

Using the elimination method, add both (1) and (2):

==> 3x = 9

==> divide by 3:

==> **x = 3**

Now to find y value using the substitution method, we will substitute with either (1) or (2)

x - 3y = 7

==> 3y = x-7

==> y = (x-7)/3 = (3-7)/3 = -4/3

==> **y = -4/3**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now